Mitochondrial calcium uniporter is required for thermogenic adaptation mediated by reactive oxygen species signaling - Suji Kim; Seung-Kuy Cha; Kyu-Sang Park; Jun Namkung (Journal of Lipid Research)
Mitochondrial Ca2+ influx via mitochondrial calcium uniporter (MCU) accelerates mitochondrial biogenesis and energy metabolism. Nevertheless, the molecular mechanism of MCU-dependent mitochondrial activation and thermogenesis in thermogenic adipose tissues remains elusive. In this study, we demonstrate that MCU governs mitochondrial functions in brown and beige adipocytes via the formation of mitochondrial reactive oxygen species (mtROS). Mice with a brown adipose tissue-specific Mcu knockout (Mcu BKO) mice exhibited decreased oxygen consumption and heat production, accompanied by downregulation of genes related to β-oxidation and thermogenesis. Furthermore, Mcu BKO mice, exhibiting a reduction in mtROS, showed defective thermogenic responses to cold exposure or β-adrenergic stimulation. Downregulation of thermogenic genes including Ucp1 in Mcu BKO mice can be rescued by exogenous ROS through AMP-activated protein kinase (AMPK) activation. Collectively, our findings suggest that MCU modulates mtROS-mediated mitonuclear signaling in thermogenic adipocytes.